Indicadores na estimativa do fluxo de digesta em bovinos de corte - Queiroz, M. F. S.; Morais, J. A. S.; Berchielli, T. T.; Malheiros, E. B.; Sader, A. P. O.; Resende, Kleber Tomás de [UNESP]; Eifert, E. C. (SciELO Espana/Repisalud, 2011)
single and double marker methods were compared in seven Nellore steers with average body weight 250 kg, and previously canullated in the rumen and duodenum. The animals were fitted with continuous-infusion pump that administered CoEDTA solutions intraruminally. In addition, a capsule containing Cr 2O 3, and other, containing external n-alkanes C 32, C 36 were inserted into the rumen of each steer. Internal markers indigestible neutral-detergent fiber and acid-detergent fiber (iNDF and iADF after 144 h in situ incubation) and internal n-alkanes C 31, C 33, C 35 were components of the diet. Steers were fed with palisade grass (Brachiaria brizantha cv. marandu) in two age of regrowth, 30 and 60 days. The duodenal flow experimental design was a factorial 2×2×12 while omasal experimental design was a factorial 2×2×4. Markers iNDF, CoEDTA and the combination Co+iNDF were efficacious to estimate duodenal dry matter flow whereas iNDF, iADF and the Co+iADF combination were all efficacious to predict omasal dry matter flow. In conclusion, the double marker method for estimation of omasal and duodenal dry matter flow was the most appropriate considering the ruminal fiber digestibility.
Markers for estimate beef cattle digesta flow
Keywords: Chromium; Coedta; Duodenal flow; Iadf; Indf; N-alkanes; Omasal flow; Animalia; Bos; Brachiaria; Urochloa brizantha